Gdynia : Kongres Eucharystyczny i Dni Morza 1939 / fotograf L. Durczykiewicz. - Durczykiewicz, Leonard (1876-1934); Durczykiewicz, Leonard (1876-1934) (L. Durczykiewicz, 1939)
Karta pocztowa z uczestnikami Kongresu.